The Effect Of Problem Based Learning On Students' Critical Thinking Abilities On The Human Digestive System Material - Putri Desiana Sipahutar; Jamalum Purba (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine the effect of the problem based learning model on students' critical thinking skills on the digestive system material. This study uses a quantitative method with a quasi experimental approach. The research design used is a two group pretest posttest. The study population includes all students of class eighth-grade of SMP Negeri 5 Medan, which consists of 11 classes. The research sample was selected using a simple random sampling technique, class VIII-4 as the experimental class and class VIII-3 as the control class. The research employed a critical thinking skills test instrument consisting of 25 multiple-choice questions. Hypothesis testing was conducted at a significance level of 0.05 with the assistance of Microsoft Excel. The results showed that the Problem Based Learning model had an effect on students' critical thinking skills. This was evidenced by the higher average posttest score of the experimental class (86.97 ± 5.85) compared to the control class (80.48 ± 6.66). The obtained N-gain value was 0.57, which falls into the moderate category. These findings indicate that the problem based learning model influences students' critical thinking skills on the topic of the human digestive system at SMP Negeri 5 Medan